2016
DOI: 10.1016/j.yrtph.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of the AmpliSeq Cancer Hotspot panel v2 in combination with the Ion Torrent Next Generation Sequencing Personal Genome Machine

Abstract: Next-Generation Sequencing is a rapidly advancing technology that has research and clinical applications. For many cancers, it is important to know the precise mutation(s) present, as specific mutations could indicate or contra-indicate certain treatments as well as be indicative of prognosis. Using the Ion Torrent Personal Genome Machine and the AmpliSeq Cancer Hotspot panel v2, we sequenced two pancreatic cancer cell lines, BxPC-3 and HPAF-II, alone or in mixtures, to determine the error rate, sensitivity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…These factors led us to sequence at high depth (1000×) and great care was taken in defining the cut‐off for calling a mutation. Previous studies have found that mutations can accurately be called if they have an AF of 5% or greater . The lowest AF mutation which we confirmed was present at 1.7%.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These factors led us to sequence at high depth (1000×) and great care was taken in defining the cut‐off for calling a mutation. Previous studies have found that mutations can accurately be called if they have an AF of 5% or greater . The lowest AF mutation which we confirmed was present at 1.7%.…”
Section: Discussionsupporting
confidence: 67%
“…TP53 coverage was used for quality control and samples with coverage <100× for each exon were considered to have failed. This reflected the coverage of all mutations and previous studies have considered a coverage of >100× to be adequate .…”
Section: Methodsmentioning
confidence: 94%
“…Anyway, due to the Ion Torrent chemistry, the homopolymer sequencing errors are known to be an issue, but the examination of our experimental results did not reveal any homopolymer-based errors or any errors caused by the position of the mutation in the amplicon. This may be due to the design of the primers used in the Cancer Hot Spot panel v2 or the location of the mutations [ 31 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the identification of mutation profile in cancer patients, it is necessary to use alternative methods of analysis with different percentages of accuracy and sensitivity to detect a mutation-driven drug resistance. Ion Torrent Personal Genome Machine has a sensitivity of results of 95% [28], while the qualitative real time PCR Rotor gene Q has a sensitivity of 99%. In our cohort of patients, the use of the two methods allowed us to identify mutations that otherwise we would have not found, with negative consequences on the clinical choices for the patients.…”
Section: Discussionmentioning
confidence: 99%